Muscular coordination during incline and level treadmill running - Swanson, S. C.; Frappier, J. P.; Caldwell, G. E. (1998)
The EMG patterns in the level conditions were very similar to those found in previous studies (e.g. McClay et al., 1990; Nummela et al., 1994). The most striking difference in the EMG patterns between the incline and level conditions was the increase in stance phase activity of the mono-articular muscles SOL, VL, and GM and the bi-articular GA and RF. Recent studies have suggested that mono-articular muscles act as energy generators, while bi-articular muscles distribute the energy across joints (Jacobs et al., 1992, 1993, 1996). In addition, estimates of muscular work have shown that energy transfer via bi-articular muscles contributes substantially to total work output during activities such as jumping and sprinting (Jacobs et al., 1996). The higher EMG levels in combination with the greater extension ROM at the hip and knee during the INC condition suggest enhanced energy generation by mono-articular extensors (GM, VL, and SOL) and energy transfer via bi-articular muscles (RF and GA). This adaptation may be necessary to meet the rigorous demands of incline running at high speeds and grades. Also, the decrease in BF and MH EMG during stance provides evidence of antagonist inhibition-possibly allowing more net energy generation during these extreme conditions. In summary, incline sprint training at 30% grade and 4.5 m/s elicited considerably greater EMG activity in several muscles of the lower extremity during stance compared to similar level running conditions. The kinematic and EMG data not only suggest higher forces and energy generation, but also indicate the feasibility that energy transport via bi-articular muscles may be enhanced in this extreme locomotion condition. As a training tool, high speed incline running is effective in increasing the activity levels in some, but not all lower extremity muscles.